2019
DOI: 10.1002/bab.1784
|View full text |Cite
|
Sign up to set email alerts
|

Weichang'an suppressed migration and invasion of HCT116 cells by inhibiting Wnt/β‐catenin pathway while upregulating ARHGAP25

Abstract: Evidence suggests that Weichang'an (WCA) inhibited the metastasis of colorectal cancer (CRC) in vitro and downregulates oncogenic β‐catenin; more intriguingly, we also found an upregulation of ARHGAP25 in this process. This study aimed to investigate the mechanisms by which WCA regulated CRC metastasis in vitro. Here, HCT116 cells were transfected with siRNAs to interfere ARHGAP25 expression. WCA decoction, XAV939 (a specific Wnt/β‐catenin pathway inhibitor), and LiCl (an activator for Wnt/β‐catenin pathway) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…[14][15][16]28 Recently, the role of ARHGAP25 in tumor cell metastasis has also been recognized. [18][19][20][21][22][23] Despite its emerging immunological and oncological importance, the post-translational control of ARHGAP25 is almost entirely unknown, prompting us to explore the regulation of this protein further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16]28 Recently, the role of ARHGAP25 in tumor cell metastasis has also been recognized. [18][19][20][21][22][23] Despite its emerging immunological and oncological importance, the post-translational control of ARHGAP25 is almost entirely unknown, prompting us to explore the regulation of this protein further.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we aimed to systematically examine the possible role of these phospho-sites in leukocytes, the cell types with the highest ARHGAP25 expression. Recently, more and more papers report the involvement of ARHGAP25 in tumor migration and metastasis, [18][19][20][21][22][23] rendering the post-translational modifications of ARHGAP25 all the more relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Many microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) have been related to cancer, and its aberrant expression has been detected in solid tumors and in hematological malignancies. [81][82][83] Many of miRNAs or lncRNAs genes are located in genomic regions associated with cancer or in fragile sites, which suggests an important role in the disease evolution. 84,85 In this sense, in recent years, the two types of RNAs have emerged as extremely useful in disease diagnosis.…”
Section: Mmps Inhibition Systemsmentioning
confidence: 99%
“…Recent studies showed that ZJW extracts can exert anti-tumorigenic effects by suppressing the canonical Wnt/β-catenin pathway in animal and cell experiments, similar to that seen with 5-HTR antagonists ( Pan et al, 2017 ). Weichang’ an (WCA) is a traditional Chinese medicinal formula used as an anticancer drug and the experimental data also showed the anti-metastatic function by blunting the activation of Wnt/β-catenin pathway and reducing the expression of MMP9 and the EMT-related protein ZEB1 ( Tao et al, 2019 ). Furthermore, TCM formulations could provide an adjunct for chemotherapy in cancer patients.…”
Section: Effect Of Tcm Formulas On Crcmentioning
confidence: 99%